2009
DOI: 10.1177/0148607109344745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Not Measuring Residual Gastric Volume in Mechanically Ventilated Patients Receiving Early Enteral Feeding

Abstract: Early EN without RGV monitoring in mechanically ventilated patients improves the delivery of enteral feeding and may not increase vomiting or ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 41 publications
3
145
0
5
Order By: Relevance
“…40,44,45 Some investigators [46][47][48][49] have suggested that the clinical utility of GRV measurements is limited. In a study 50 in 205 patients treated with mechanical ventilation who were receiving enteral nutrition, adverse events such as ventilator-associated pneumonia and vomiting did not differ between patients in whom GRV purposely was not measured and patients in whom GRV was measured. Current nutritional guidelines 25 suggest that enteral feedings should not be withheld if a patient has a GRV less than 500 mL and no other indications of feeding intolerance.…”
Section: Administration Of Enteral Nutrition and Pressure Ulcersmentioning
confidence: 93%
“…40,44,45 Some investigators [46][47][48][49] have suggested that the clinical utility of GRV measurements is limited. In a study 50 in 205 patients treated with mechanical ventilation who were receiving enteral nutrition, adverse events such as ventilator-associated pneumonia and vomiting did not differ between patients in whom GRV purposely was not measured and patients in whom GRV was measured. Current nutritional guidelines 25 suggest that enteral feedings should not be withheld if a patient has a GRV less than 500 mL and no other indications of feeding intolerance.…”
Section: Administration Of Enteral Nutrition and Pressure Ulcersmentioning
confidence: 93%
“…The rationale for measurement of GRVs is to reduce the risk for aspiration pneumonia by either ceasing or modifying the enteral feeding strategy based on the detection of excess gastric residuals. The inherent controversy is that observational and interventional studies have not consistently confirmed a relationship between the measurement of GRVs (with thresholds ranging from 200 mL to no monitoring of GRVs) and outcomes of vomiting, aspiration, or pneumonia [597][598][599][600][601][602][603]. In our systematic review, we identified one multicenter non-inferiority trial of 452 critically ill patients who were randomized to not monitoring GRVs versus monitoring GRVs at 6-h intervals [602].…”
Section: We Recommend Against the Use Of Omega-3 Fattymentioning
confidence: 99%
“…33,37 Specific determination of what constitutes a high GRV is unclear in the literature, and practices for assessing and addressing high GRVs vary. [38][39][40][41] Uncertainty regarding the assessment and treatment of high GRVs makes clinical decision making regarding management of GRVs difficult for practitioners.…”
Section: Intolerance Of Enteral Nutritionmentioning
confidence: 99%
“…20,38,40 In experimental studies, GRV did not correlate with aspiration, vomiting, or ventilator-associated pneumonia, 50,51 yet it continues to be standard to routinely monitor GRVs in practice. Measurement of GRV is subjective and is affected by the patient's position, the feeding tube diameter, the syringe size, and the clinician performing the measurement.…”
Section: Assessment Of and Response To Grvsmentioning
confidence: 99%